2018
DOI: 10.1002/sdtp.12388
|View full text |Cite
|
Sign up to set email alerts
|

P‐158: Study on Dispersant Influence of Color Characteristic Degradation of colorant Material for Wide Color Gamut†

Abstract: Color characteristic degradation of color filter photoresist is occurred under high temperature, high humidity, and strong light environments. The effect of dispersant in color filter photoresist to color characteristic degradation was studied, and it depends on the dispersant in color PR, which has been experimentally verified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…For overcoming these problems, many researches about process technique and electrical property have been reported with the development of high coloring new colorants. 6 A. Kim et al 8 reported it found out that color characteristic of green colorant in liquid crystal cell was decreased under high temperature, high humidity, and strong light stresses. The degradation of color characteristic was verified by placing liquid crystal cell made of color chip coated with color PR under the environment for 24 hours.…”
Section: Electrical Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…For overcoming these problems, many researches about process technique and electrical property have been reported with the development of high coloring new colorants. 6 A. Kim et al 8 reported it found out that color characteristic of green colorant in liquid crystal cell was decreased under high temperature, high humidity, and strong light stresses. The degradation of color characteristic was verified by placing liquid crystal cell made of color chip coated with color PR under the environment for 24 hours.…”
Section: Electrical Propertymentioning
confidence: 99%
“…2 Color materials, which are applied in display panel, are closely related to colorant synthesis, 3,4 dispersion, 5 CF process, 6 and reliability of product. 7,8 Therefore, design colorants for wide color gamut (WCG) technology are important from basic research of color material to improving property of product ( Figure 1). J. Namgoong et al 3 studied effective structure for improving dispersion through the synthesis of dyes with various functional groups such as bulk, polarity, and ionic properties.…”
Section: Introductionmentioning
confidence: 99%